Pembentukan Kreativitas Peserta Didik Menggunakan Metode Bermain Peran di SD Alam Perwira Purbalingga - Ali Wardana; Nurfuadi Nurfuadi (Departement of Mathematics Education, 2023)
Departing from the phenomenon of low creativity in general, more specifically the low creativity in the world of education. Many efforts have been made by the government on this matter, starting from the issuance of laws to changing the curriculum which was carried out many times starting from the Active Student Learning Method (CBSA) to the implementation of the 2013 Curriculum (Kurtilas), but the results have not been maximized. So it is necessary to establish the creativity of students in continuous learning. It is this effort to form student creativity that has been carried out by SD Alam Perwira Purbalingga.This study aims to describe and analyze the formation of students' creativity using the role playing method at SD Alam Perwira Purbalingga. This research is a type of field research with a phenomenological approach that is descriptive in nature, namely a research method that seeks to describe and interpret objects as they are. The object in this study is the formation of students' creativity using the role playing method. Data collection techniques using observation, interviews, and documentation. Researchers in analyzing the data used the model developed by Miles and Huberman which included data reduction, data presentation, and drawing conclusions. Data analysis was obtained through data collection, data reduction, data presentation and drawing conclusions. Checking the validity of the data using source triangulation techniques.The results of this study indicate that the formation of student creativity using the role playing method at SD Alam Perwira Purbalingga is carried out by playing the role of a mini restaurant, this activity is applied in learning which includes planning the implementation of learning, preparing teaching materials, preparing learning media, preparing learning strategies, preparing resources learning, and evaluation. The results obtained were that the formation of student creativity using the role playing method at SD Alam Perwira Purbalingga has succeeded in forming several creativity including imagination creativity, language creativity, mathematical creativity, and artistic creativity.